2020
DOI: 10.1055/s-0040-1702187
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following Revision Total Knee Arthroplasty Septic versus Aseptic Failure: A National Propensity-Score-Matched Comparison

Abstract: Although periprosthetic joint infection (PJI) has been hypothesized to increase the risk of complications following revision total knee arthroplasty (TKA), strong evidence linking the two is lacking. The aim of this study was to determine whether PJI is an independent risk factor for inpatient perioperative complications, and increased resource use in patients undergoing revision TKA. We relied on the US Nationwide Inpatient Sample (NIS) to identify patients with PJI or non-PJI treated with revision TKA betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…However, similar to our findings, a study conducted by Choi and Bedair [14] reported age greater than 65 years independently increased the risk of mortality within both aseptic and septic revision TKA (odds ratio [OR] 1.13, 95% confidence interval [CI]: 1.05-1.21, P < .001). Additional studies have also implicated advanced age in increased risk of poor clinical outcomes, including the need for higher acuity care [31,32], PJI [8], and inhospital mortality [3]. The latter findings support those of the present study and highlight the need to consider advanced age in risk stratification for revision TKA.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, similar to our findings, a study conducted by Choi and Bedair [14] reported age greater than 65 years independently increased the risk of mortality within both aseptic and septic revision TKA (odds ratio [OR] 1.13, 95% confidence interval [CI]: 1.05-1.21, P < .001). Additional studies have also implicated advanced age in increased risk of poor clinical outcomes, including the need for higher acuity care [31,32], PJI [8], and inhospital mortality [3]. The latter findings support those of the present study and highlight the need to consider advanced age in risk stratification for revision TKA.…”
Section: Discussionsupporting
confidence: 87%
“…An increase in revision TKAs among patients older than 80 years has also been observed [7]. This growth in revision arthroplasty will contribute to an estimated annual burden of $13 billion by 2030 [8,9]. Previous literature surrounding revision TKA has investigated survivorship [10,11], complications [12,13], and mortality [14], yet these studies have been limited by heterogeneity of procedures and One or more of the authors of this paper have disclosed potential or pertinent conflicts of interest, which may include receipt of payment, either direct or indirect, institutional support, or association with an entity in the biomedical field whichmay be perceived to have potential conflict of interest with this work.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, although previous studies have shown worse outcomes when comparing PJI to aseptic complications [7,8], our study found no difference between rates of new diagnosis between patients who suffered aseptic complications vs. infection, as well as between a subset of these 2 cohorts who subsequently went on to revision surgery. The authors posit one explanation for this is the inclusion of only acute PJI in the analysis.…”
Section: Discussioncontrasting
confidence: 82%
“…Literature on the consequences of PJI and aseptic failure after total joint arthroplasty (TJA) has been well documented. These complications are associated with poor clinical outcomes, often requiring staged management and leaving patients with poor overall health-related quality of life [ 3 , 6 , 7 ]. Furthermore, compared with aseptic revisions, revisions for PJI have been shown to have a significantly higher risk of major postoperative complications including death, sepsis, non-home discharge, readmissions, and prolonged hospital length of stay [ 8 ].…”
Section: Introductionmentioning
confidence: 99%